Al-Ittijāh al-Kalāmīy Inda Ḥasan Ḥanafi: Dirāsah Taḥlīliyyah Naqdiyyah fī Ḍaui al-‘Aqīdah al-Islāmiyyah - Anisa Nabela; Risma Nur Baiti Tsani (Kalimah: Jurnal Studi Agama dan Pemikiran Islam, 2023)
This study is inspired by the fact that Muslims have historically lived following the spirit and syari'ah of Islam. However, with the growth of human thinking patterns and frameworks, it is not surprising that there is still a negative influence through the war of intellectual invasion, whether from outside or from within Islam. Many societal problems, including those of politics and economics, as well as justice and freedom, do not have solutions according to Hassan Hanafi. He is a contemporary Egyptian figure who aims to revive new steps in modern Islamic culture. This research is included in the category of theological research, and it seeks to investigate Hassan Hanafi's main concepts and thoughts regarding his Kalam Science, as well as the patterns that influence it. In this study, the author uses three research methodologies: descriptive, analytical, and critical methods. Beginning with the author's exposition of Hassan Hanafi's beliefs in his writings, then observing Kalam's thoughts from his works, criticizing them in light of Mutakallim's and other Muslim philosophers' perspectives on ‘Aqīdah Islāmiyyah. According to this study, Hassan Hanafi has made changes ancient Islamic theology to support religious reforms and create people's rights. The Reformation's goal is to place humans at the centre of life, to shift from theocentric to anthropocentric, and from the hereafter to the world orientation, and to advocate for liberation theology that seeks to raise the rights of downtrodden people. Thus, it becomes very evident that Hassan Hanafi's approach to understanding ancient Islamic theology is extremely impacted by the legacy of Western thought and is therefore not in agreement with the ‘Aqīdah Islāmiyyah, which still upholds the naṣ of the Qur'an rather than prioritizing rationality.